Ethnic discrimination, asking for fair treatment, and poor self-rated health: a gender stratified analysis of 13,443 Korean Chinese waged workers in South Korea - Hayoung Lee; Ji-Hwan Kim; Garin Lee; Hyelin Lee; Mita Huq; Delanjathan Devakumar; Seung-Sup Kim (BMC, 2024)
Abstract Background In South Korea, Korean Chinese workers experience ethnic discrimination although they share physical similarities and ethnic heritage with native-born Koreans. This study aimed to examine whether perceived ethnic discrimination is associated with poor self-rated health and whether the association differs by gender among Korean Chinese waged workers in South Korea. Methods We conducted a pooled cross-sectional analysis using data of 13,443 Korean Chinese waged workers from the Survey on Immigrants' Living Conditions and Labor Force conducted in 2018, 2020, and 2022. Based on perceived ethnic discrimination, asking for fair treatment, and subsequent situational improvement, respondents were classified into the following four groups: "Not experienced," "Experienced, not asked for fair treatment," "Experienced, asked for fair treatment, not improved," and "Experienced, asked for fair treatment, improved." Poor self-rated health was assessed using a single question "How is your current overall health?" We applied logistic regression to examine the association between perceived ethnic discrimination and poor self-rated health, with gender-stratified analyses. Results We found an association between ethnic discrimination and poor self-rated health among Korean Chinese waged workers. In the gender-stratified analysis, the "Experienced, not asked for fair treatment" group was more likely to report poor self-rated health compared to the "Not experienced" group, regardless of gender. However, gender differences were observed in the group stratified by situational improvements. For male workers, no statistically significant association was found in the "Experienced, asked for fair treatment, improved" group with poor self-rated health (odd ratios: 0.87, 95% confidence intervals: 0.30-2.53). Conversely, among female workers, a statistically significant association was observed (odd ratios: 2.63, 95% confidence intervals: 1.29-5.38). Conclusions This study is the first to find an association between perceived ethnic discrimination and poor self-rated health, along with gender differences in the association between situational improvements after asking for fair treatment and poor self-rated health among Korean Chinese waged workers in South Korea.